Evaluation of the profile of hospitalizations for decompensated systemic arterial hypertension in a health macro-region in the state of Maranhão, Brazil (Research, Society and Development, 2021)
The present study aims to analyze the profile of patients who were hospitalized for decompensation of Primary Arterial Hypertension within the northern health macro-region of Maranhão through an epidemiological study in the SIH/SUS, considering the period 2016-2020. As a methodology, a documental evaluation study was carried out, using public data from the statistical tools of the DATASUS network, which were obtained through access as an individual according to the access rights granted by Law No. 12,527/2011. The study population was made up of the northern health macro-region of Maranhão, which encompasses around 4,084,650 inhabitants and which made use of hospital services. Data were filtered by quantitative and care characteristics, using subfilters of individual characteristics and care character, which encompassed all procedures performed in the health network belonging to the macro-region of northern Maranhão, considering the historical series of the last 5 years for the hospital care (2016-2020). The data found in this study demonstrate that female patients have had a greater tendency to hospitalizations due to Systemic Arterial Hypertension and even despite this trend, the lethality for males is substantially higher, also having a positive correlation of deaths with the increase of age. Thus, this study hopes to contribute to a better understanding of the impacts of Primary Arterial Hypertension on health systems.